2014
DOI: 10.1590/s1984-29612014083
|View full text |Cite
|
Sign up to set email alerts
|

Infection of the heart of Pimelodus ornatus (Teleostei, Pimelodidae), by Myxobolus sp. (Myxozoa, Myxobolidae)

Abstract: The phylum Myxozoa Grassé, 1970, consists of a heterogenous group of around 50 genera that are worldwide disseminated in a wide variety of aquatic media. In the present study, 43 specimens of Pimelodus ornatus were collected from an adjacent area to the Cachoeira do Arari municipality on Marajó Island, in the Brazilian state of Pará, in 2013. Macroscopic analysis showed the presence of whitened plasmodia located in the cardiac muscle and also in the region between the bulbus arteriosus and atrium cordis. Micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
0
5
1
Order By: Relevance
“…Myxobolus spp. parasitized 65% of gills of the fish examined, a value higher than that reported in the heart of Pimelodus ornatus, from the Arari Waterfall, which had a prevalence of 13.9% in the 43 specimens analyzed (MATOS et al, 2014). LACERDA et al (2013) explained that the discrimination of the fish parasitic fauna can be based on premise that the different biogeographic regions showed a range of possibilities for the parasitic fauna structure in the host, thus explaining the differences in parasites prevalence in their hosts.…”
Section: )contrasting
confidence: 55%
“…Myxobolus spp. parasitized 65% of gills of the fish examined, a value higher than that reported in the heart of Pimelodus ornatus, from the Arari Waterfall, which had a prevalence of 13.9% in the 43 specimens analyzed (MATOS et al, 2014). LACERDA et al (2013) explained that the discrimination of the fish parasitic fauna can be based on premise that the different biogeographic regions showed a range of possibilities for the parasitic fauna structure in the host, thus explaining the differences in parasites prevalence in their hosts.…”
Section: )contrasting
confidence: 55%
“…Among myxozoans, freshwater histozoic Myxobolus species are recognized for their strict or high host-organ/tissue specificity [5], infecting a large variety of fishes within a wide geographical range [6][7][8][9]. Regarding pathogenecity, previous studies conducted in South American freshwater fishes reported Myxobolus species to cause considerable pathological alterations such as lymphocytic meningoencephalomyelitis, myocarditis of the heart, perivascular edema in the interlamellar area and deformation and compression of capillaries of the gill lamellae [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…For example, VELASCO et al (2012) observed inflammation in the musculature of the palate of Gobioides broussonnetii LACEPÈDE, 1800, which caused a generalized necrosis of the parasitized muscle, consistent with the presence of necrotizing myositis. MATOS et al (2014) described a discreet inflammatory reaction and multifocal degeneration of the cardiac fibers by Myxobolus sp. in Pimelodus ornatus KNER, 1858 from Marajó Island.…”
Section: Discussionmentioning
confidence: 99%